Vulnerability: The Human Depth of a Principle of Bioethics (Revista Iberoamericana de Bioética, 2023)
Vulnerability is an essential principle in European bioethics, given that it precedes and has priority over other principles. This principle, stated in the Barcelona Declaration, is also specified in the Universal Declaration on Bioethics and Human Rights. This broadens its horizon from a European to a universal level. For these reasons, we need to take time to carefully consider its meaning. For this task, this article offers a summary of the key questions and presents the DNA of vulnerability in eight contexts: cultural, social, institutional, anthropological, emotional, relational, biographical and professional.
Keywords: vulnerability; bioethics; relational anthropology; fragility; emotion